Teachers' Coping Strategies in Facing Burnout due to Administrative Burden at Swasti Sari Foundation Secondary School, Archdiocese of Kupang, Alor Branch - Maria Gabriela Walman Ratu; Sutapa, Mada (Universitas Muhammadiyah Pontianak, 2026)
Teachers are increasingly burdened by administrative responsibilities that may contribute to burnout and affect teaching quality. This study examines teachers' burnout caused by administrative workload and the coping strategies they employ in foundation-based secondary schools in Alor, Indonesia. A qualitative phenomenological approach was used through interviews, observations, and document analysis involving principals, curriculum coordinators, and teachers. The findings reveal that excessive administrative demands trigger emotional exhaustion, reduced motivation, and depersonalization. Teachers mainly adopt emotion-focused coping strategies, which provide temporary relief but fail to address organizational causes. The study highlights the need for school management to redesign administrative systems and strengthen institutional support to enhance teacher well-being and educational quality.